Density dependence of solar emission lines of boron-like ions - Dwivedi B.N.; Raju P.K. (My University, 2025)
Steady state level density of 20 levels of boron-like ions, Mg viii and Si x, have been computed as a function of electron density and temperature. We have accounted for collisional and spontaneous radiative processes. Photo-excitation between the two levels of the ground term has also been considered. Using the computed level density, line intensities have been obtained as a function of electron density and temperature. In case of Mg viii, line intensity ratio I(430.47)/I(436.62) is found to be electron density sensitive. Likewise other pairs of lines namely, I(75.03)/I(74.86), I(315.02)/I(430.47), and I(315.02)/I(335.23) are also found to be density sensitive. Similar density sensitive line intensity ratios have been found for Si x. Absolute line fluxes from these ions at earth distance have been computed and are found to be comparable with values obtained, using various satellite and rocket measurements. © 1980 D. Reidel Publishing Co.